SOCIAL CAPITAL OF THE FISHERMEN COMMUNITY IN TELUK NIBUNG SUB DISTRICT, TANJUG BALAI CITY, NORTH SUMATERA PROVINCE - Siburian, Mona Lolita; Kusai, Kusai; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in February - March 2020 in Teluk Nibung sub district, Tanjug Balai city, North Sumatera Province. The location of this research was chosen deliberately (purposive). Based on the results of research conducted on social capital of the fishermencommunity in Teluk Nibung sub district, Tanjug Balai city, North Sumatera Province, then the form of trust that forms the social capital of the fishermen community consists of elements of the element of trust itself which among other things is honesty that is they are open about operational costs when at sea, fairness that is the existence of strict rules and strict sanctions, egalitarian attitudes that are not there is a distinction between fishermencommunities, tolerance that is mutual respect for the opinions of fellow fishermencommunities, generosity that is willingness to help fellow fishermen communities who experience disaster. How to maintain an honest attitude and positive thinking, no jealousy and vengeance, dare to be responsible for the mistakes made, and also sincere in helping others.Keywords: Social Capital,Social Capital, Fishermen Communities